Экспериментальное изучение сплавов системы Al–Ni–C при высоких давлениях и температурах - Туркевич, В.З.; Гаран, А.Г.; Ткач, С.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Phase equilibria at a pressure of 7,0 GPa and temperature from 1600 to 1910 ⁰С in the
Al–Ni–C system have been studied. The samples subjected to high pressure and temperature were
quenched and examined by X-ray diffraction, metallographic analysis and scanning electron microscopy. From quenched products the diamond phase has been extracted. The diamond formation region is situated between the binary Ni–C system and Al₀,₅Ni₀,₅–C section in the phase diagram of the ternary Al–Ni–C system. The diamond phase is mainly dendritic crystals with octahedral faces.